Health disparities among under-served populations implications for research, policy and praxis - Notaro, Sheri R. (Emerald, 2012)
Health Disparities Among Under-served Populations: Implications for Research, Policy and Praxis, focuses on a topic of national concern. Both disparities in health status and in health care reflect the continuing power of race, social class, and gender as forces that define the social determinants of health and the social, biological, and physical environments where groups live. Chapters focus on key issues that include substance abuse, psychological coping, trauma, infant mortality, HPV, environmental hazards, teen pregnancy, homeless youth, racism, discrimination, and cultural competence. The scholars who have contributed to this volume showcase their insight and keen analyses of these pressing issues through a variety of lenses, including but not limited to, sociology, economics, psychology, education, public health, history, urban studies, nursing, and environmental activism. This anthology critically examines the devastating impact of race, class, and gender on the health and health care of African Americans, Latinos and American Indians, with particular focus on children and adolescents.
Includes index.
Keywords: Education -- Multicultural Education.; Education -- Educational Policy & Reform -- General.; Educational strategies & policy.; Multicultural education.; Minorities -- Medical care -- United States.; Minorities -- Health and hygiene -- United States.; elektronické knihy; electronic books